Determinan of Audit Fee In Indonesia Islamic Bank - Harahap, Aulia Rahman; Siregar, Saparuddin; Nurlaila, Nurlaila (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
This study aims to examine the link between audit fees and the following variables: 1) the number of audit committee meetings; 2) the size of the internal audit; 3) the number of internal audit assignments; and 4) the number of branches. This study is an example of causal associative research, a kind of quantitative research that uses secondary data acquired from research sample websites. According to the study's findings, audit fees are influenced by the following factors in the following orders: 1) the size of the internal audit has an effect on audit fees; 2) the number of internal audit assignments has no effect on audit fees; and 4) the number of branches has an effect on audit fees.